Kontrol Sosial Orang Tua dan Perilaku Remaja dalam Penggunaan TikTok: Studi di Desa Blang Panyang, Lhokseumawe - Sanusi Sanusi; Cut Rifa Azzahra; Yusrijal Abdar; Syahrul Ridha; Puspita Annaba Kamil (Jurnal Community, 2026)
Social control is a planned or unplanned process aimed at encouraging, guiding, and even forcing people to comply with prevailing norms. Parents who provide attention, emotional support, and responsiveness to their children's needs tend to form secure bonds. The objectives of this study are to describe and analyze adolescent behavior in using TikTok social media and to describe and analyze parental social control over adolescent behavior in using TikTok social media in Blang Panyang Village, Lhokseumawe City. Data collection techniques in this study were interviews and documentation. The sample consisted of 18 informants. The results show that adolescents' behavior in using TikTok social media is predominantly consumptive, involving watching viral videos and then seeking popularity by creating viral content, such as dance challenges, even though it is not on the For Your Page (FYP). Adolescents spend 5-7 hours on TikTok social media. Generally, parents in Blang Panyang Village exercise preventative social control over their children's TikTok use through persuasive means through socialization. There is also repressive social control through coercive means through force. Therefore, adolescents' behavior on TikTok is characterized by consuming viral videos, spending 5-7 hours on TikTok, and following viral content. Social control is implemented both preventively through persuasion and repressively through coercion.